PENERAPAN PENDEKATAN SAINTIFIK DALAM PEMBELAJARAN IPS DI SMP NEGERI 2 ANJIR PASAR BARITO KUALA KALIMANTAN SELATAN - Zainuddin Zainuddin (JURNAL SOCIUS, 2015)
The scientific approach is believed to be the golden bridge and the development of attitudes, skills, and knowledge of learners. The application of scientific approach is a challenge for teachers through the development of students' activity is observed, ask, gather information, reasoning and mengkomunikasikan.IPS with Scientific Approach. The learning is not just memorize concepts, year or mere facts, but trying to connect these concepts to produce a full understanding, so the concept is easy to learn dipahami.Penelitian conducted using qualitative methods. The purpose of this study to describe the learning plan IPS with the scientific approach, describe the implementation of social studies lesson with scientific approaches and describes the evaluation of learning social studies in SMP Negeri 2 Anjir Pasar Barito Kuala South Kalimantan. The study of SMP Negeri 2 Anjir Market in applying scientific approaches in teaching social studies showed that teachers in these schools are already making plans to learning social studies scientific approach. Some stages of implementation with the approach of scientific learning IPS also has to be applied in SMP Negeri2 Anjir Markets, Results eveluasi learning by providing about suitable materials given, the result of 18 students, 16 were completed with a value above KKM = 70 and 2 students incomplete, with the classical completeness is 88.89%.Keywords: scientific approach, learning IPS